A longitudinal study on the impact of subjective exclusion on changes in self-esteem: the mediating effect of perceived income inequality - Wan-Kyeong Park; Soo-Bi Lee (PLoS ONE, 2025)
This study explored the impact of the subjective exclusion perceived by adults on the development trajectory of self-esteem and verified the mediating role of perceived income inequality. We analyzed data from the 2017–2020 Korea Welfare Panel Study on 1,410 20–59-year-old research participants. Descriptive statistics were used to analyze the key variables and research participants’ general characteristics. A structural equation model investigated how the change trajectory of self-esteem and subjective exclusion affected the development trajectory of self-esteem via perceived income inequality. First, greater perceived subjective exclusion is associated with higher perceived income inequality, which acts as the mediator variable. Furthermore, the higher the perceived subjective exclusion, the lower the initial self-esteem; this gap increased over time. Second, perceived income inequality did not significantly impact initial self-esteem but positively significantly affected self-esteem’s rate of change, showing a wide variation. These findings suggest the necessity of social support systems and policy interventions to restore self-esteem, a cornerstone of mental health, among individuals experiencing social exclusion. Additionally, given that perceived income inequality impacts self-esteem, efforts to address social structural inequalities should be strengthened alongside clinical interventions.